Study of the Factors Responsible for the Dropouts from the BSc Programme of Indira Gandhi National Open University - Bharat Inder Fozdar (Athabasca University Press, 2006)
A sample of dropout learners enrolled in the B.Sc. programme of School of Sciences, Indira Gandhi National Open University, India was surveyed to study the factors which influenced them to withdraw from the programme. The research indicates that the major reasons for dropout are the distance of study centre from the residence of learner, insufficient support from study centre and more time consuming courses of the programme. The results of this study are significant from the points of view of improving the present instructional and delivery strategies of B.Sc. Programme. This will also help in reducing the students' dropout rate for this programme by implementing timely interventions at the different stages of study.